2015
DOI: 10.3109/15368378.2015.1043556
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electromagnetic field on cyclic adenosine monophosphate (cAMP) in a human mu-opioid receptor cell model

Abstract: During the cell communication process, endogenous and exogenous signaling affect normal as well as pathological developmental conditions. Exogenous influences such as extra-low-frequency electromagnetic field (EMF) have been shown to effect pain and inflammation by modulating G-protein receptors, down-regulating cyclooxygenase-2 activity, and affecting the calcium/calmodulin/nitric oxide pathway. Investigators have reported changes in opioid receptors and second messengers, such as cyclic adenosine monophospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…We chose an ELF-EMF of 5 Hz, 0.4 mT field to test on MSCs/pericytes because we have used this magnetic field strength and frequency in past experiments to measure its effect on various cytokines and transcription factors involved in pain- and inflammation-related mechanisms in vitro. 4 , 5 Although we demonstrated an anti-inflammatory secretion profile in cells treated with ELF-EMF, others have reported harmful cellular effects, depending on the energy state of the field. 10 Bioelectromagnetics, the study of how living organisms interact with EMF, investigates the interaction between electrons, atoms, ions, and molecules present in all living matter, and how they are influenced by electromagnetic interactions.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We chose an ELF-EMF of 5 Hz, 0.4 mT field to test on MSCs/pericytes because we have used this magnetic field strength and frequency in past experiments to measure its effect on various cytokines and transcription factors involved in pain- and inflammation-related mechanisms in vitro. 4 , 5 Although we demonstrated an anti-inflammatory secretion profile in cells treated with ELF-EMF, others have reported harmful cellular effects, depending on the energy state of the field. 10 Bioelectromagnetics, the study of how living organisms interact with EMF, investigates the interaction between electrons, atoms, ions, and molecules present in all living matter, and how they are influenced by electromagnetic interactions.…”
Section: Discussionmentioning
confidence: 70%
“…Extremely low frequency electromagnetic fields (ELF-EMF) penetrate through the skin into the body’s deep tissue to affect cell function. 1 3 Studies report ELF-EMF to be effective in the treatment of pain and inflammation 4 7 and also tissue regeneration and wound healing. 8 , 9 Evidence shows that mechanisms of action include Ca 2+ ion flux, and expression/activation of Ca 2+ ion binding proteins such as calmodulin, increase the cytosolic Ca 2+ concentration to affect signaling pathways targeting tissues such as bone, cartilage, and nerve for pain regulation and tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Years ago, it was found that increased levels of cAMP in sensory neurons indeed lead to a transient enhancement of transmitter release in the synaptic connection between sensory and motor neurons, which was regarded as a biochemical mechanism for short-term and long-term changes [13, 40]. Some studies have suggested that signaling pathways involving cAMP participate in inflammation and injury sensitization [41, 42]. Here, our study found an increased number of cAMP-positive cells in the ACC of pain memory model rats.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid receptors relay opioid stimulation through G i or G o -mediated inhibitory intracellular signal transduction pathways [18], which may suppress G olf or G s -induced cAMP signaling in cells. For example, pharmacological activation of OPRM1 and OPRD1 blocks dopamine DRD1- or adenosine A2A-receptor-induced activation of adenylyl cyclase and reduces the production of cAMP in SPNs [51]. A reduction of cAMP levels may suppress protein kinase A (PKA) activity and leads to an aberrant activation of extracellular signal-regulated kinases (ERK1/2) in the generation of LID [52, 53].…”
Section: Opioid Signaling In the Pathogenesis Of Lidmentioning
confidence: 99%